2007
DOI: 10.1897/06-346r.1
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial control region variation in bank voles (Clethrionomys glareolus) is not related to Chernobyl radiation exposure

Abstract: Abstract-Three previous studies at Chernobyl, Ukraine, documented elevated mitochondrial DNA diversity in bank voles (Clethrionomys glareolus) from radioactively contaminated sites. Little evidence was found to link patterns of diversity in contaminated areas to radiation exposure, but the experimental design precluded discriminating among alternative explanations for elevated diversity in exposed groups. Reference sites selected for the studies were relatively distant from contaminated sites and, additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…Only two haplotypes exclusive to populations in radioactive sites were detected, despite extensive sampling over multiple years. Data from additional uncontaminated sites thus alters the conclusions drawn from previous Chernobyl research [4,6,16,17], in which radioactively contaminated sites were shown to harbor a greater number of endemic lineages.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Only two haplotypes exclusive to populations in radioactive sites were detected, despite extensive sampling over multiple years. Data from additional uncontaminated sites thus alters the conclusions drawn from previous Chernobyl research [4,6,16,17], in which radioactively contaminated sites were shown to harbor a greater number of endemic lineages.…”
Section: Discussionmentioning
confidence: 87%
“…The investigative tactic is considered to be particularly valuable in instances when preexposure data are unavailable but the nature, extent, and temporal boundaries of the contamination event are documented. Such methodology has been represented as a practical approach for assessing the causal relationships between multigenerational exposure to polluted environments and biological effects [1–4]. Selecting reference sites and/or populations useful for comparative purposes can be complicated, however, both because of the numerous factors that can influence the demographic characteristics of a species and because the relative impact of these factors differs across taxonomic lines [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the availability of over 1,000 mtDNA control region sequences sampled from individuals of C. glareolus from multiple studies (see Table 1 and Supporting Information Appendix S2), use of these sequences has primarily been restricted to investigating the associated Puumala virus (Dekonenko et al, 2003;Johansson et al, 2008;Razzauti, Plyusnina, Niemimaa, Henttonen, & Plyusnin, 2012) or the effects of Chernobyl radiation (Matson, Rodgers, Chesser, & Baker, 2000;Meeks et al, 2007;Meeks, Chesser, Rodgers, Gaschak, & Baker, 2009;Wickliffe et al, 2006) on C. glareolus. Figure 2b indicates diversity values generally reflective of the aforementioned complexity; however, regionally restricted sampling does not enable accurate phylogeographical inferences to be made using the control region sequences available here.…”
Section: Clethrionomys [= Myodes] Glareolusmentioning
confidence: 99%
“…Admittedly, the literature reports heterogeneous results on DNA damage and mutation rate in organisms living in areas around Chernobyl with low levels of contamination [46][49]. However, the susceptibility of sperm to DNA damage stems partly from the down-regulation of DNA repair systems during late spermatogenesis [24].…”
Section: Introductionmentioning
confidence: 99%